Development of Hydrogel Fatigue Sensor. (13th December 2018) - Iijima, Tetsuro; Inoue, Shota; Saito, Azusa; Tamate, Hideaki; Khosla, Ajit; Kawakami, Masaru; Murasawa, Go; Furukawa, Hidemitsu
Abstract : When high-strength gels are industrially used, predicting the life expectancy by grasping the behavior of destruction and fatigue when repetitively deformed in places used as gels means that comfort and safety as a product In this study, we developed a fatigue monitoring gel which can measure the deformation frequency and fatigue degree of the gel and carried out a fatigue test as a physical property evaluation.